What is distributed SQL? : scale, resilience, and data locality for modern applications - Modderman, Paul; Walker, Jim; Custer, Charles (O'Reilly Media, Inc., 2022)
Globally available resources have become the status quo. They're accessible, distributed, and resilient. Our traditional SQL database options haven't kept up. Centralized SQL databases, even those with read replicas in the cloud, put all the transactional load on a central system. The further away that a transaction happens from the user, the more the user experience suffers. If the transactional data powering the application is greatly slowed down, fast-loading web pages mean nothing. In this report, Paul Modderman, Jim Walker, and Charles Custer explain how distributed SQL fits all applications and eliminates complex challenges like sharding from traditional RDBMS systems. You'll learn how distributed SQL databases can reach global scale without introducing the consistency trade-offs found in NoSQL solutions. These databases come to life through cloud computing, while legacy databases simply can't rise to meet the elastic and ubiquitous new paradigm. You'll learn: Key concepts driving this new technology, including the CAP theorem, the Raft consensus algorithm, multiversion concurrency control, and Google Spanner How distributed SQL databases meet enterprise requirements, including management, security, integration, and Everything as a Service (XaaS) The impact that distributed SQL has already made in the telecom, retail, and gaming industries Why serverless computing is an ideal fit for distributed SQL How distributed SQL can help you expand your company's strategic plan.